Gender diversity in leadership and firm performance: evidence from the Czech Republic - Hedija, Veronika; Němec, Daniel (Journal of Business Economics and Management, 2021)
The paper examines the effect of gender composition of executive body on financial performance and financial health of the firms. The data of more than thousand Czech travel agencies and tour operators for the period 2008–2015 was employed in the paper. To test the relationship between firm performance and gender diversity in leadership, the regression model was applied. After using alternative measurement for gender diversity of executive body and controlling for firm size, firm age, executive body size, leverage ratio and industry, the results have shown that the gender composition of executive body has no statistically significant effect on both firm performance and financial health of firms. The study deepens empirical knowledge about the relationship between gender diversity of executive body and corporate performance and financial health and brings new insights into the link between these phenomena in the Czech Republic. First published online 17 November 2020